A Deacetylation–Diazotation–Coupling Sequence: Palladium‐ Catalyzed CC Bond Formation with Acetanilides as Formal Leaving Groups. Issue 2 (1st February 2013) - Schmidt, Bernd; Berger, René
Abstract Acetanilides can be deacetylated and diazotized in situ, and subsequently used in Pd‐catalyzed coupling reactions without isolation of the diazonium intermediate. Heck reactions, Suzuki cross‐coupling reactions, and a Pd‐catalyzed [2+2+1] cycloaddition have been investigated as terminating CC bond‐forming steps of this one‐flask sequence. The sequence does not require the exchange of solvents or removal of by‐products between the individual steps, but proceeds by addition of reagents and catalysts in due course.